A randomised controlled comparison of enteral versus parenteral nutritional support post allogeneic haematopoietic cell transplantation. Issue 3 (June 2015) - Andersen, Sarah; Kennedy, Glen; Banks, Merrilyn
Summary: Background and aims: Nutritional support during allogeneic haematopoietic progenitor cell transplantation (HPCT) is imperative to prevent malnutrition and poorer patient outcomes. However, there is little literature on the most efficacious approach, leading to wide variation in the use of enteral (EN) and parenteral (PN) feeding across HPCT units. This study aimed to determine the tolerability and efficacy of EN versus PN in patients undertaking allogeneic HPCT. Methods: A randomised controlled trial was conducted from September 2011 to January 2013. Patients were randomized to receive either EN (nasogastric) or PN if nutrition support was required, however those with severe gastro-intestinal toxicity, including severe mucositis, were excluded from randomisation. If patients did not tolerate the type of feeding given they were swapped to the alternate route. Results: Nine patients were able to be randomized between EN (n = 5) and PN (n = 4). The patients randomized to EN all required changing to PN due to gastro-intestinal intolerance (p ≤ 0.01). None of the patients receiving PN required changing to EN. Conclusions: This study demonstrates that due to the significant gastrointestinal toxicity, EN was not feasible to commence when oral intake became inadequate. This study was registered with the Australian New Zealand Clinical Trials Registry (ANZCTR), Trial Number ACTRN12611001084976.